A historical review of HIV prevention and care initiatives in British Columbia, Canada: 1996‐2015. Issue 1 (19th September 2017) - Olding, Michelle; Enns, Ben; Panagiotoglou, Dimitra; Shoveller, Jean; Harrigan, P Richard; Barrios, Rolando; Kerr, Thomas; Montaner, Julio S. G.; Nosyk, Bohdan
Abstract: Introduction : British Columbia has made significant progress in the treatment and prevention of HIV since 1996, when Highly Active Antiretroviral Therapy (HAART) became available. However, we currently lack a historical summary of HIV prevention and care interventions implemented in the province since the introduction of HAART and how they have shaped the HIV epidemic. Guided by a socio‐ecological framework, we present a historical review of biomedical and health services, community and structural interventions implemented in British Columbia from 1996–2015 to prevent HIV transmission or otherwise enhance the cascade of HIV care. Methods : We constructed a historical timeline of HIV interventions implemented in BC between 1996 and 2015 by reviewing publicly available reports, guidelines and other documents from provincial health agencies, community organizations and AIDS service organizations, and by conducting searches of peer‐reviewed literature through PubMed and Ovid MEDLINE. We collected further programmatic information by administering a data collection form to representatives from BC's regional health authorities and an umbrella agency representing 45 AIDS Service organizations. Using linked population‐level health administrative data, we identified key phases of the HIV epidemic in British Columbia, as characterized by distinct changes in HIV incidence, HAART uptake and the provincial HIV response. Results and Discussion : In total, we identified 175 HIV prevention and care interventions implemented in BC from 1996 to 2015. We identify and describe four phases in BC's response to HIV/AIDS: the early HAART phase (1996–1999); the harm reduction and health service scale‐up phase (2000–2005); the early Treatment as Prevention phase (2006–2009); and the STOP HIV/AIDS phase (2010‐present). In doing so, we provide an overview of British Columbia's universal and centralized HIV treatment system and detail the role of community‐based and provincial stakeholders in advancing innovative prevention and harm reduction approaches, as well as "seek, test, treat and retain" strategies. Conclusions : The review provides valuable insight into British Columbia's HIV response, highlights emerging priorities, and may inform future efforts to evaluate the causal impact of interventions.